Lythraceae endémicas del Perú - León, Blanca (2006)
The Lythraceae are represented in Peru by 10 genera and 30 species (Brako & Zarucchi, 1993; Ulloa Ulloa et al., 2004), mostly herbs and shrubs. Here we recognize one endemic taxon in the genus Cuphea. This endemic has been found in areas of the Very Humid Montane Forest region, between 2400 and 3000 m elevation. It has not yet been registered within the Peruvian protected areas system.